Development of novel FP-based probes for live-cell imaging of nitric oxide dynamics - Emrah Eroglu (Nature Portfolio, 2016)
Nitric oxide is a volatile free radical second messenger with a large number of biological effects. Here Eroglu et al. develop genetically encoded fluorescent biosensors for nitric oxide and use them to visualise subcellular nitric oxide dynamics in single cells.